2014
DOI: 10.1038/jid.2013.435
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Multiple Complex Rearrangements Associated with Deletions in the 6q23-27 Region in Sézary Syndrome

Abstract: Figure 3g of this article was published with the legend labels inverted. The open bar should read ''Wild type'' and the solid bar should read ''TLR4 deficient''. The corrected figure appears below. The publisher regrets the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The 6q23‐27 region, recurrently deleted in SS, was reported in European, which involved in bi‐ and monoallelic deletions of A20 , suggesting that it may be a linker between the altered immune response and leukemogenesis . A20 is also a putative tumor suppressor in the T cell malignancy .…”
Section: Resultsmentioning
confidence: 99%
“…The 6q23‐27 region, recurrently deleted in SS, was reported in European, which involved in bi‐ and monoallelic deletions of A20 , suggesting that it may be a linker between the altered immune response and leukemogenesis . A20 is also a putative tumor suppressor in the T cell malignancy .…”
Section: Resultsmentioning
confidence: 99%
“…In human hepatocellular carcinoma (HCC), hAIG1 expression was correlated with HCC patient survival rates and thus can be used as a novel biomarker for the progression of HCC [4]. Other studies also indicated that AIG1 is involved in cancer-related processes; e.g., AIG1 can form complexes with either nuclear factor 1/B in salivary adenoid cystic carcinoma or Golgi SNAR complex member 1 in T cell lymphoma [5,6]. Zhu et al reported that when KBM7 mucells were treated with chlorpyrifos, AIG1 was required for resistance to these environmental toxicants [7].…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal instability plays an important role in the pathogenesis and prognosis of this lymphoma and genetic instability has associated with a poor prognosis [19]. Recurrent regional gains are usually observed at 17q, 8q and 17p, whereas regional losses have been observed at 17p, 10q, 6q, 9q, 10p, 9p and 19p [20]. These regions are likely to contain genes involved in the development of SS.…”
Section: Introductionmentioning
confidence: 99%